2021
DOI: 10.2147/ijgm.s327186
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Early Outcomes of Hospitalized COVID-19 Patients with End-Stage Kidney Disease in Saudi Arabia

Abstract: Background The prognosis of the novel coronavirus disease 2019 (COVID-19) may be poor in patients with end-stage kidney disease (ESKD). Limited information is available on the clinical characteristics and outcomes of such patients in Arab countries. The present study aimed to address this gap. Methods This retrospective cohort study included 101 patients with ESKD who were hospitalized for COVID-19 between May 1, 2020 and December 31, 2020 at King Fahad Central Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
(39 reference statements)
0
8
1
Order By: Relevance
“…Different rates have been reported from different localities in Saudi Arabia as Riyadh (4.27%), 93 Mecca (2.7%), 94 Jazan (19%). 95 Moreover, variable rates were reported worldwide. Higher rates of mortality were observed in European and American countries.…”
Section: Discussionmentioning
confidence: 99%
“…Different rates have been reported from different localities in Saudi Arabia as Riyadh (4.27%), 93 Mecca (2.7%), 94 Jazan (19%). 95 Moreover, variable rates were reported worldwide. Higher rates of mortality were observed in European and American countries.…”
Section: Discussionmentioning
confidence: 99%
“…High D-dimer levels, neutrophilia, lymphocytopenia, and high blood urea nitrogen levels were also significant risk factors for death in this population. The most common complications resulting in death were septic shock, respiratory failure, and respiratory distress syndrome ( Hakami et al, 2021 ). As for the symptoms, the most commonly reported were fever, shortness of breath, and cough.…”
Section: High-risk Populationmentioning
confidence: 99%
“…As for the symptoms, the most commonly reported were fever, shortness of breath, and cough. The majority of the patients were admitted to the hospital general ward with 17% only requiring ICU and intubation ( Hakami et al, 2021 ). Al Maghrabi et al reported four cases of fully vaccinated solid organ transplants (three renal and one liver), infected with SARS-CoV-2.…”
Section: High-risk Populationmentioning
confidence: 99%
“…Several studies set in SA have described the clinical characteristics of COVID-19 patients, though most of them were limited by small sample size [ 16 , 17 ]. The overall mortality rate among critically ill patients in SA was estimated to range between 25% and 42% and was higher among patients on mechanical ventilation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%